PREDICTING FROST HEAVE IN ROAD EMBANKMENTS: A MACHINE LEARNING APPROACH INTEGRATING SOIL COMPOSITION AND WEATHER - Балашова, Юлія; Балашов, Андрій (SWorldJournal, 2025)
Frost heave in road embankments is a critical issue in cold-region geotechnical engineering, leading to surface distresses, differential settlements, and maintenance challenges. As climate patterns evolve, accurate frost heave prediction becomes increasin